Self-peeling of frozen water droplets upon impacting a cold surface - Fang, Wen-Zhen (2022)
Freezing of water droplets impacting a cold substrate is a commonly encountered circumstance impairing the performance and safety of various applications. Active methods of ice removal such as heating or mechanical means are energy intensive and inconvenient. Here, we report a passive ice removal method via harvesting the thermal-mechanical stress of ice, leading to the self-peeling of frozen water droplets upon impacting a cold substrate. We find that the frozen ice completely self-peels and is then easily removable from a cold hydrophobic surface whiles the ice exhibits cracking and remains firmly sticky to a hydrophilic surface. The peeling behaviors of frozen water droplets are then scrutinized by varying the subcooling degree, impact parameters and wettability. Moreover, we develop a theoretical model to characterize the peeling and bending behaviors of the ice and also provides a simple criterion to predict the occurrence of complete self-peeling, facilitating the design of anti-icing surfaces.